2000
DOI: 10.1016/s1097-2765(00)00074-5
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Ubiquitination Machinery to Target the Degradation of Specific Cellular Proteins

Abstract: The functional characterization of a specific gene, or its protein product, often relies on assessing the consequences of its elimination, usually accomplished by gene knockout, ribozyme, antisense, or RNA-mediated interference (RNAi) technologies. The selective degradation of cellular proteins is mediated primarily by the ubiquitin-proteasome pathway. Manipulation of the ubiquitin-dependent proteolytic machinery to eliminate specific gene products at the protein level has been previously attempted with some s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
114
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(115 citation statements)
references
References 20 publications
1
114
0
Order By: Relevance
“…As ␤-catenin is also required for the normal growth of the cell, targeted cells can not survive when the ␤-catenin gene is completely silenced with current knockout technologies (18). Targeting proteins to SCF ubiquitination machinery promises an alternative gene-silencing tool (19)(20)(21). In this study, we demonstrate that SCF provides a powerful means of eradicating pathogenic ␤-catenin in CRC.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…As ␤-catenin is also required for the normal growth of the cell, targeted cells can not survive when the ␤-catenin gene is completely silenced with current knockout technologies (18). Targeting proteins to SCF ubiquitination machinery promises an alternative gene-silencing tool (19)(20)(21). In this study, we demonstrate that SCF provides a powerful means of eradicating pathogenic ␤-catenin in CRC.…”
mentioning
confidence: 74%
“…These features have prompted several earlier studies to explore SCF ubiquitin-conjugation machinery as a possible protein knockout tool (19)(20)(21). One study demonstrated SCF-mediated degradation of retinoblastoma protein (20). A very recent study showed that an artificially designed ''Protacs'' effectively eradicated a targeted methionine aminopeptidase 2 protein (21).…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained with the ODC͞AZ system and other previously reported approaches for inducing proteasome-dependent degradation of specific proteins (2,3,(5)(6)(7)(8) should be interpreted with understanding that the particular protein ligand chosen may have multiple cellular targets, including unknown or unanticipated protein targets in addition to known interacting proteins intended for targeted degradation. Thus, phenotypes created by these targeted protein-degradation methods could potentially reflect the loss of expression of several interacting proteins.…”
Section: Discussionmentioning
confidence: 97%
“…1). Accordingly, expression systems have been described in which whole proteins or fragments constituting functional proteininteraction domains or peptide ligands are expressed as chimeric fusion proteins together with modified versions of ubiquitin (2,3), ubiquitin ligases (e.g., HECT-domain-containing proteins) (4), or adapter proteins that associate with ubiquitin ligase complexes (e.g., F-box proteins of Skp1͞cullin͞F-box protein complexes) (5)(6)(7)(8), with the intention of inducing polyubiquitination of cellular proteins that bind these chimeric proteins, thus creating holes in pathways that reveal cellular phenotypes.…”
mentioning
confidence: 99%
“…In most of these cases, intrabodies were used as means to alter the intracellular trafficking and localization of their targets, for example, by trapping oncogene products (e.g., epidermal growth factor receptor and ErbB2) that were destined for cell surface expression in the endoplasmic reticulum or isolating transcription factors (e.g., Cyclin E) in the cytoplasm. Alternatively, intrabodies have been used to block protein-protein or protein-nucleic acid interactions (51), to directly promote cell death by inducing apoptosis-related proteolysis cascade (52 -54), or, albeit indirectly, to facilitate selective degradation of target proteins by recruitment to the ubiquitin-proteasome pathway (55). In this study, by targeting the enzymatic activity of an intracellular kinase (i.e., Etk) with an intrabody, we showed that we could modulate the role of a kinase plays in cell transformation in an extremely specific manner.…”
Section: Discussionmentioning
confidence: 99%